Minimum sand transportation conditions in multiphase pipelines: an assessment exercise - Zhou, Zhang; Lao, Liyun (BHR Group, 2017)
In offshore multiphase gas and oil pipelines, sand management is a vital task to prevent sand accumulative blockage and maintain pipeline mechanical integrity. This paper reports a study on the minimum transport condition (MTC) issue for typical subsea gas and liquid pipelines as a part of sand management strategy. A literature review was conducted on published prediction methods wrt sand transportation. A selective set of these models were benchmarked against the published experimental data and evaluation of model performances has been reported. The exercise started with the models of MTC in single phase liquid flows and followed by the models in gas/liquid flows. An Excel-based prediction tool was developed aiming to provide a straightforward method to obtain “sand -deposit-free” operating envelope for a multiphase flow pipeline during initial screening. Two methods were incorporated in this Excel based tool to assess MTCs in gas-liquid multiphase flow, including (i) modified King’s correlation (2016) and (ii) Danielson’s correlation (2007). The modified King’s model is found to be more flexible to account for the uncertainty in terms of definitions on “sand transport conditions” in multiphase flow.